BMC322- A RATIONALLY-DESIGNED LIVE BACTERIAL CONSORTIUM BASED ON MICROBIOME FUNCTIONAL GENOMIC ANALYSIS FOR TREATMENT OF IBD. (21st January 2021) - Polonsky, Omri; Meshner, Shiri; Eshar, Shiri; Ben-Shabat, Sheerli Kruger; Tirosh, Osnat; Haber, Elran; Ringel, Yehuda
Abstract: The mechanisms by which the intestinal microbiome affects intestinal inflammation and disease activity in IBD is not clear. Most of the current data on the association between the intestinal microbiome and IBD is focusing on the intestinal microbial taxa and very little is known about the functionality of the microbiome in this condition. Aim: To construct a live bacterial consortium for reduction of intestinal inflammation in IBD based on a high-resolution functional microbial analysis, and its association with anti-inflammatory processes. Methods: Fecal metagenomics samples (n=581) and corresponding fecal calprotectin (FCP) levels from patients with Crohn's disease and Ulcerative Colitis were downloaded from the NCBI (SRA SRP057027, http://hmpdacc.org, SRA SRP002163 and SRP056641 (BioProject PRJNA275349)). Computational analysis was performed using PRISM (Biomica Ltd, Rehovot Israel), a proprietary metagenomics analysis platform integrating assembly-based and reference-based analyses for functional genomics profiling and utilizing BioCOGS, Biomica's internal comprehensive catalogue of microbial gene-orthology groups. We compared microbial functions between subjects based on severity of inflammation (FCP<70 vs FCP >250 and FCP >250 vs FCP <250) and identified microbial functions associated with low inflammation (FDR 0.1). Validation of the anti-inflammatory activity of BMC322 was performed using a DSS-induced colitis mouse model. Results: Out of the dozens of identified functions, 32 were related to host anti-inflammatory processes, intestinal barrier integrity and colonocyte function. Our functional microbiome investigation has pointed to novel metabolic mechanisms by which specific strains may attenuate mucosal inflammation. Using functional annotations, we infer the biological processes governing microbe-host interactions contributing to reduced inflammation, and identify 16 bacteria of which 4 strains comprise the full array of the identified microbial functions associated with lower disease severity. These strains comprise BMC322- a novel live-bacterial consortium for inflammation reduction in IBD. The anti-inflammatory activity of these strains was validated in in-vitro studies and demonstrated efficacy in preliminary a mouse model of DSS-induced colitis; including shortening period of recovery, disease activity index and fecal lipocalin 2. Conclusion: High-resolution functional genomics profiling of the gut microbiome enables identification of microbial-derived functions relevant to inflammatory disease activity, and microbial strains bearing specific inflammation-reduction activity. These strains have provided the basis for the construction of a 4-strain consortium for intervention in IBD. Preliminary work has validated the anti-inflammatory activity of these strains and their potential as novel therapeutic modality for IBD.